Proposal for a regulation establishing a framework for screening of foreign direct investments into the European Union of september’17 - Esplugues Mota, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Foreign investment flows have increased steadily in the last decades, although the financial crisis and the role played by certain emerging economies, mainly PRC, are negatively influencing them. A change of trend is not ascertainable yet, but some backlash against foreign direct investment exists in particular countries. The development of mechanisms of control of foreign investment shows this change of attitude. The situation is especially relevant in the European Union because of the embryonic condition of the Common Investment Policy. The publication of the Proposal for a Regulation establishing a framework for screening of foreign direct investments into the European Union reflects the relevance of the topic at the same time that offers a first text for debate.
Keywords: Foreign Direct Investment; Control of Foreign Direct Investment; National Security; Common Commercial and Investment Policy; Screening systems of evaluation of foreign direct investment